Keterwakilan Perempuan pada Pemilihan Anggota Dewan Perwakilan Rakyat Kabupaten Tulang Bawang Barat pada Pemilihan Umum (Pemilu) 2019 - Hervina, Ari; Hertanto, Hertanto; Warganegara, Arizka (Utan Kayu Publishing, 2021)
The breakthrough to achieve justice in the political field is the implementation of an affirmative action system, which is a system used globally to enable women to play their role, especially in the world of politics. The purpose of this research is to find out, analyze and explain what factors influence women's representation in the West Tulang Bawang Regency DPRD election results in 2019 and to find out, analyze and explain strategies for increasing women's representation in PDIP, Nasdem Party and Gerindra Party. As for those who became respondents in this study amounted to 7 people. The results of this research are 1) The factors that influence women's representation in the Legislative Election DPRD Tulang Bawang Barat Regency are 3 (three), namely political education, political communication and political culture and the most dominant factor influencing is